A Mediterranean of Remnants: Jewish and Arabo-Islamic Sicily in Vincenzo Consolo - Pappalardo, Salvatore (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2025)
In his novels, writer and intellectual Vincenzo Consolo (1933-2012) intricately maps the intersecting histories of Sicily’s Mediterranean civilizations. This article discusses what I call Consolo’s “Mediterranean of remnants,” highlighting the author’s approach to Sicily’s historical narratives as he seeks to recover and emphasize the often neglected Jewish and Arabo-Islamic legacies embedded in the island’s cultural fabric. Through his narrative archeology, Consolo unearths and reinterprets layers of Sicilian history, reimagining his own lineage in the process and challenging traditional views of Sicilian identity. The exploration begins with an analysis of Jewish Sicilian history as depicted in Consolo’s novels Nottetempo, casa per casa and La ferita dell’aprile, linking these stories to his personal reflections on his suspected Jewish ancestry. The study then shifts to examining his representation of Sicily’s Arabo-Islamic heritage, particularly through his aesthetics of grafting, which he uses to explain the cultural hybridity of Sicilians. Consolo’s works challenge the erasure of Sicilian Jewish and Muslim histories, advocating for a richer, more inclusive understanding of Sicilian identity that acknowledges its profound connections to the broader Mediterranean basin. By weaving these complex narratives together, Consolo not only enriches our understanding of Sicilian history and literature but also contributes to a more nuanced appreciation of the Mediterranean’s multifaceted cultural legacy. This study reaffirms his literary and philosophical significance, positioning his works as essential readings for anyone seeking a deeper understanding of the Mediterranean’s intercultural dynamics.